Facile synthesis of nitrogen-doped carbon nanosheets with hierarchical porosity for high performance supercapacitors and lithium–sulfur batteries1. Issue 36 (28th September 2015) - Yu, Xiaoliang; Zhao, Jianfeng; Lv, Ruitao; Liang, Qinghua; Zhan, Changzhen; Bai, Yu; Huang, Zheng-Hong; Shen, Wanci; Kang, Feiyu
<x xml:space="preserve">Abstract</x> Nitrogen-doped hierarchical porous carbon nanosheets were prepared through co-pyrolysis of magnesium citrate and potassium citrate and the following NH3 treatment.